Anterior Shoulder Dislocations in Busy Emergency Departments: The External Rotation Without Sedation and Analgesia (ERWOSA) Method May Be the First Choice for Reduction. Issue 47 (November 2015) - Janitzky, Angelika A.; Akyol, Can; Kesapli, Mustafa; Gungor, Faruk; Imak, Arefe; Hakbilir, Oktay
Abstract : Abstract: Shoulder joint is the most common joint requiring reduction by emergency physicians. Successful reduction is based on the overcoming of resistance of the shoulder muscles. Pain is the most important factor in resistance increase and sedation; analgesia and, in certain cases, intra-articular anesthesia are preferred for reduction. The external rotation (ER) method can provide successful reduction without causing an increase in muscle resistance if applied slowly and gently. The aim of this study was, therefore, to determine the usefulness of the ERWOSA method in the reduction of acute anterior shoulder dislocations (AASDs). This was a retrospective descriptive study. The records of patients admitted to the emergency department with anterior shoulder dislocation between 2009 and 2011 were reviewed for demographic data, sedation, analgesia, and discharge times. Patients were then divided into ERWOSA (n = 80) and external rotation and sedation-analgesia (ERASA, n = 59) groups, with regard to the application of SA (sedation-analgesia). The study data were analyzed using SPSS version 22.0 software for Windows. Numerical data were presented as mean ± standard deviation and categorical data as rates. A total of 139 patients were included in the study. The patients' average age was 35 ± 14 years, 108 (77.7%) were male. Successful reduction rates for 59 male and 21 female patients in the ERWOSA group were 83% and 66.7% (78.7% total success), respectively. Successful reduction rates for 49 male and 10 female patients in the ERASA group were 87.7% and 90% (88.1% total success), respectively. The length of stay of the ERWOSA and ERASA groups in emergency services were found to be significantly different, with 55 ± 17 and 118 ± 23 minutes for each group, respectively. There were no complications. The ER method can be used in reduction of anterior shoulder dislocations without sedation and analgesia, if applied slowly enough to overcome the resistance of shoulder muscles. The ERWOSA method causes both a significant decrease in the length of stay of patients in the emergency department results in negating the possibility of adverse drug effects. In busy emergency departments, male patients with anterior shoulder dislocation are particularly suitable candidates for ERWOSA.